Cooperative effect of oncogenic MET and PIK3CA in an HGF-dominant environment in breast cancer - Liu, Shuying (Mol Cancer Ther, 2018)
There is compelling evidence that oncogenic MET and PIK3CA signaling pathways contribute to breast cancer. However, the activity of pharmacological targeting of either pathway is modest. Mechanisms of resistance to these monotherapies have not been clarified. Currently commonly used mouse models are inadequate for studying the HGF-MET axis because mouse HGF does not bind human MET. We established human HGF-MET paired mouse models. In this study, we evaluated the cooperative effects of MET and PIK3CA in an environment with involvement of human HGF in vivo. Oncogenic MET/PIK3CA synergistically induced aggressive behavior and resistance to each targeted therapy in an HGF-paracrine environment. Combined targeting of MET and PI3K abrogates resistance. Associated cell signaling changes were explored by functional proteomics. Consistently, combined targeting MET and PI3K inhibited activation of associated oncogenic pathways. We also evaluated the response of tumor cells to HGF-stimulation using breast cancer patient-derived xenografts (PDXs). HGF-stimulation induced significant phosphorylation of MET for all PDX lines detected to varying degrees. However, the levels of phosphorylated MET are not correlated with its expression, suggesting that MET expression level cannot be used as a sole criterion to recruit patients to clinical trials for MET-targeted therapy. All together, our data suggests that combined targeting of MET and PI3K could be a potential clinical strategy for breast cancer patients, where phosphorylated MET and PIK3CA mutation status would be biomarkers for selecting patients who are most likely to derive benefit from these co-targeted therapy.